KAITAN INDEPENDENT LEARNING DENGAN KEMAHIRAN BELAJAR SISWA DIKAJI DARI OPEN ENDED QUESTION DALAM MATERI PERSAMAAN GARIS SINGGUNG - Juan Antonio Siahaan; Munaldus Munaldus; Dona Fitriawan (Jurnal AlphaEuclidEdu, 2023)
This study aims to determine the relationship of independent learning with students' learning skills assessed from open ended questions in the material of tanggent equations in SMAN 7 Pontianak. The method used is bivariate correlation. The sample used was 30 students of grade 12 science 4 at SMAN 7 Pontianak. The instruments used were independent learning questionnaires and student learning proficiency tests. the results of the study showed that grade 12 science 4 students were in the medium category of Independent Learning, in the moderate category of Student Learning Proficiency, and there was no relationship Between Independent Learning and Student Learning Proficiency with a Spearman Rank value of 0.11.